The effects of internet usage on business sustainability of small technology-based rural business in Malaysia - Mohamad, Mohd Amin; Chin, Othman (Science Publishing Corporation Inc, 2018)
This study examines the effects of internet usage on the business sustainability of small technology based rural business. It adopts the quantitative study methodology using self –administered survey method. The findings of this study shows that internet usage has positive and significant effects on the business sustainability of small rural businesses in this study. This study utilized IBM SEM AMOS 21 in analyzing the effects of internet usage on business sustainability of small technology based rural business in Malaysia. This study has contributed to the literature of small business entrepreneurship by adding perspective of internet usage among the technology-based rural business and its effects on business sustainability.